STEADY STATE CONDITION PREDICTION OF ECONOMIC GROWTH IN EAST JAVA REGION - Sutikno Sutikno (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2019)
The quality of development of a country or region is not only seen from the high level of economic growth, but also the higher level of economic growth produced by people in a country or region. One of the economic development debates in East Java in the last few decades is the imbalance of development between regions. This article focuses its analysis on the value of